2018
DOI: 10.1080/15427528.2018.1531800
|View full text |Cite
|
Sign up to set email alerts
|

Learning from farmers to improve sorghum breeding objectives and adoption in Mali

Abstract: Many efforts have been made to improve sorghum [Sorghum bicolor (L.) Moench] varieties, but adoption of improved varieties remains low. Sorghum has diverse panicle architecture and grain qualities that vary within and between races, and utilization and adoption may depend on these traits. Recent efforts in West Africa to improve local guinea race germplasm as a base material have diversified potential options: there are breeding materials with a range of panicle types with increased grain number per panicle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Interactions took place through various on-farm and on-station participatory breeding activities (Weltzien et al 2020). Farmers also explored the sorghum diversity available with breeders by visiting research stations or on-farm plots (Diakite 2003;Siart 2008) and identified and prioritized preferred traits for future improvements (Weltzien et al 2006;2008;Diallo et al 2018).…”
Section: The Development Of the Sorghum Network In Malimentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions took place through various on-farm and on-station participatory breeding activities (Weltzien et al 2020). Farmers also explored the sorghum diversity available with breeders by visiting research stations or on-farm plots (Diakite 2003;Siart 2008) and identified and prioritized preferred traits for future improvements (Weltzien et al 2006;2008;Diallo et al 2018).…”
Section: The Development Of the Sorghum Network In Malimentioning
confidence: 99%
“…Targeted studies of specific topics, such as farmers' seed systems and trait preferences (Diakité 2003;Siart 2008;Ehret 2010, unpublished work;Deu et al 2014;Diallo et al 2018), as well as women's role in sorghum production and use (Isaacs et al 2018;Rattunde et al 2018) were undertaken. Also, characterizations of agro-ecological and climatic factors influencing crop-production and crop improvement research (Abdulai et al 2012;Herrmann et al 2013) were conducted.…”
Section: The Development Of the Sorghum Network In Malimentioning
confidence: 99%
“…Sorghum farmers in the Sudanian and Sahelian zone of WA, stretching across Senegal, Mali and Burkina Faso, predominantly cultivate Guinea-race varieties or landraces that possess the required panicle (lax and drooping with wide glume opening at maturity) and grain quality (hard corneous endosperm, low decortication, and grain storage losses) and a suite of adaptation traits (Weltzien et al, 2018). It was therefore necessary for breeders to develop female parents based on local germplasm to produce hybrids with key adaptation and grain quality traits, required for adoption by farmers (Toure and Scheuring, 1982;Diallo et al, 2018).…”
mentioning
confidence: 99%
“…The high significant variability observed in grain yield has also been reported by several previous studies on sorghum [3] [26] [27] [28]. However, the 100 grains weight trait which was used to estimate seed size and grain yield before harvest, according to Deffan et al [24] showed low variability.…”
Section: Discussionmentioning
confidence: 54%